Bacteriocins as natural weapon against cancer: in vitro, in vivo, and in silico perspectives - Birhan Getie Assega; Kindu Nibret Tsegaye; Temesgen Mitiku; Berhanu Andualem Tsehai (Discover Applied Sciences)
Abstract Background Cancer, characterized by uncontrolled cell proliferation, metastasis, and angiogenesis, remains a leading cause of death worldwide. Conventional cancer therapies leading to significant side effects. Consequently, there is an urgent need for alternative, targeted treatments. Bacteriocins, ribosomally synthesized antimicrobial peptides produced by bacteria, have emerged as promising anticancer agents. They exhibit selective toxicity towards cancer cells, owing to their cationic, amphiphilic, and membrane-active properties, which target the negatively charged membranes of cancer cells. Objective This review aims to explore bacteriocins as alternative anticancer agents, focusing on their mechanisms of action, discuss the challenges associated with their use, and explore future perspectives for their application in cancer therapy. Methods Recent in vitro, in vivo, and in silico studies on bacteriocins' anticancer effects are reviewed. Bacteriocins' ability to differentiate cancer cells from normal cells, their mechanisms of action, and their potential for clinical application were assessed. Results Bacteriocins demonstrate anticancer properties by exploiting differences between cancer and normal cells, including membrane charge, lipid composition, and metabolic conditions. They induce apoptosis, disrupt mitochondrial integrity, affect angiogenesis, and modulate immune responses. In vitro studies show promising results with bacteriocins like nisin, inhibiting cancer cell growth and inducing apoptosis. In vivo studies, such as those with microcin E492, demonstrate significant tumor reduction in animal models. Docking analyses suggest strong binding affinities between bacteriocins and cancer-related targets. Conclusion Bacteriocins are promising tools for targeted cancer therapy with minimal side effects on healthy cells. They may enhance existing cancer therapies by inducing apoptosis and improving immune responses. Overcoming challenges to use bacteriocins as anticancer agents and exploring their potential in clinical setting is crucial.